The Child Kidnapping and Abuse by Gang-criminals and the Legitimate Custody of Minor to Parents After Rescue and use of Geofencing to Arrest the Absconding Criminals: Dr Aftab Ahmad Malik, Dr Waqar Azeem, Dr Mujtaba Asad - Dr Aftab Ahmad Malik; Dr Waqar Azeem; Dr Mujtaba Asad (International Journal for Electronic Crime Investigation, 2022)
This paper mainly focuses on the custody of a minor child, abducted and abused by criminals from the place of parental residence. The cases regarding the kidnapping of minor young girls and teenage women are increasing rapidly. The modus operandi of criminals varies from case to case. In some cases criminals torture the abducted minors, rape, and kill them; while in some other cases to escape from law enforcement agencies, they arrange “forced-illegal-fake” marriages under threat of life. In most of the offenses, an organized rich Gang of criminals is tangled and involved. The Gang members are given different responsibilities to perform and commit the crime by the leader of the Gang. They have also the backing of the most effective personalities, who safeguard them in the existing system and such personalities remain effective and hidden. Therefore, the victim and the family do not get justice from any corner. The Gang and the “effective personality” invest huge amounts of money in “red light areas” or the sale of limbs like kidneys, hearts or livers, etc inland or abroad. However, the abductee undergoes a lot of torture and gang rape. Secondly, the authors focus on and stress the need for strong legislation so that criminals are punished when their guilt is proven and also not bailed out for nonbailable offenses. Thirdly and most importantly, the abductee must be handed over to the parents after recovery from the criminal Gang. This paper presents a case study of an abducted school-baby, who has not been handed over to the parents for the last six months. The faults of the legal system in Pakistan require to be overviewed, revamped, and overhauled. The antagonistic behavior of Police and investigating officers is also required to be modified, which adversely affects the merits of the case in courts of law.